Targeted acidosis mediated delivery of antigenic MHC-binding peptides - Kelly, Joey J.; Ankrom, Emily T.; Newkirk, Sarah E.; Thévenin, Damien; Pires, Marcos M. (Frontiers in Immunology, 2024)
Cytotoxic T lymphocytes are the primary effector immune cells responsible for protection against cancer, as they target peptide neoantigens presented through the major histocompatibility complex (MHC) on cancer cells, leading to cell death. Targeting peptide-MHC (pMHC) complex offers a promising strategy for immunotherapy due to their specificity and effectiveness against cancer. In this work, we exploit the acidic tumor micro-environment to selectively deliver antigenic peptides to cancer using pH(low) insertion peptides (pHLIP). We demonstrated the delivery of MHC binding peptides directly to the cytoplasm of melanoma cells resulted in the presentation of antigenic peptides on MHC, and activation of T cells. This work highlights the potential of pHLIP as a vehicle for the targeted delivery of antigenic peptides and its presentation via MHCbound complexes on cancer cell surface for activation of T cells with implications for enhancing anti-cancer immunotherapy.